Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS Menggunakan Strategi Information Search Kelas IV SDN 23 Bukik Apik Kecamatan Baso - Habibi, Rahman Walid; Zuryanty, Z. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research was motivated by the low learning outcomes of students. The aim of this research is to describe the improvement in student learning outcomes using the Information Search learning strategy in class IV of SDN 23 Bukik Apik, Baso District. This research is classroom action research (PTK) which uses qualitative and quantitative approaches. The research was carried out in two cycles, namely cycle I was held in 2 meetings and cycle II was held in 1 meeting. The results of the research showed an increase in: a) Teaching Module cycle I with an average of 85.4% (B), cycle II 95.83% (SB), b) Implementation of the educational aspect of cycle I with an average of 79.65% (B), cycle II 90.62% (SB), while implementation in the student aspect of cycle I with an average of 81.21% (B), cycle II 90.62% (SB), c) Assessment of students In improving learning outcomes in cycle I, the average was 73.12 (C) and in cycle II the average was 84.95 (B). It can be concluded that using this learning strategy can improve student learning outcomes